Baseline predictors of negative and incomplete pleural cytology in patients with suspected pleural malignancy – Data supporting 'Direct to LAT' in selected groups. (July 2019) - Tsim, Selina; Paterson, Sarah; Cartwright, Douglas; Fong, Christopher J.; Alexander, Laura; Kelly, Caroline; Holme, Jayne; Evison, Matthew; Blyth, Kevin G.
Highlights: Asbestos exposure is an independent predictor of negative pleural fluid cytology. A malignant CT is an independent predictor of negative pleural fluid cytology. Failure of predictive marker testing in pleural fluid is common in ovarian cancer. Negative pleural fluid cytology is associated with an increased time to diagnosis. Abstract: Objectives: Negative effusion cytology is more common in certain forms of Malignant Pleural Effusion (MPE) and results in pathway delay. Local Anaesthetic Thoracoscopy (LAT) is extremely sensitive and safe but cannot be offered to all. A stratified pathway, including 'Direct to LAT' in selected cases could enhance patient experience but requires reliable baseline predictors of unhelpful cytology, including both negative (no malignant cells) and incomplete results (malignant cells identified but predictive markers failed), since pleural biopsies will be required in the latter for optimal management. This retrospective analysis of a prospective multi-centre study, sought to identify baseline features for pathway rationalization. Materials and methods: 363/638 (57%) of patients recruited to the DIAPHRAGM study (ISRCTN10079972) were included. Prospective data, including final diagnoses, asbestos exposure and fluid cytology results were supplemented by retrospective Computed Tomography (CT) and predictive marker reports. Independent predictors of negative and incomplete cytology were determined by multivariable logistic regression. Contingency tables were used to assess diagnostic value of cytology in associated phenotypes. Results: 238/363 (66%) patients were diagnosed with MPE (18 tumour types). Fluid cytology was negative in 151/238 (63%) and independently associated with asbestos-exposure (Odds Ratio (OR) 5.34) and a malignant CT (OR 2.25). When both features were recorded the sensitivity and negative predictive value of fluid cytology were 19% (95% CI 11–30%) and 9% (95% CI 4–20%)), respectively. Cytology was incomplete in 34/238 (14%), i.e. 47% of positive cytology cases) but was not associated with any baseline feature. ORs for incomplete cytology in Ovarian, Breast, Renal and Lung Cancer were 83, 22, 21 and 9, respectively. Conclusion: Negative cytology is extremely likely in patients with asbestos exposure and a malignant CT report. A 'Direct-to-LAT' approach may be appropriate in this setting. No baseline predictors of incomplete cytology were identified.